Quad-Quaternion MUSIC for DOA Estimation Using Electromagnetic Vector Sensors. (12th April 2009) - Gong Gong, Xiaofeng Xiaofeng; Liu Liu, Zhiwen Zhiwen; Xu Xu, Yougen Yougen
Abstract : A new quad-quaternion model is herein established for an electromagnetic vector-sensor array, under which a multidimensional algebra-based direction-of-arrival (DOA) estimation algorithm, termed as quad-quaternion MUSIC (QQ-MUSIC), is proposed. This method provides DOA estimation (decoupled from polarization) by exploiting the orthogonality of the newly defined "quad-quaternion" signal and noise subspaces. Due to the stronger constraints that quad-quaternion orthogonality imposes on quad-quaternion vectors, QQ-MUSIC is shown to offer high robustness to model errors, and thus is very competent in practice. Simulation results have validated the proposed method.